Oxfendazole flukicidal activity in pigs - Ortiz-Oblitas, P. (2014)
Although oxfendazole (OFZ) is a well know broad-spectrum benzimidazole anthelmintic, the assessment of its potential trematodicidal activity remains unexplored. OFZ administration at single high doses has been recommended to control Taenia solium cysticercus in pigs. The current study investigated the flukicidal activity obtained after a single high (30 mg/kg) oral dose of OFZ in pigs harbouring a natural Fasciola hepatica infection. Sixteen (16) local ecotype pigs were randomly allocated into two (2) experimental groups of 8 animals each named as follow: Untreated control and OFZ treated, in which animals received OFZ (Synanthic®, Merial Ltd., 9.06% suspension) orally at 30 mg/kg. At seven (7) days post-treatment, all the animals were sacrificed and direct adult liver fluke counts were performed following the WAAVP guidelines. None of the animals involved in this experiment showed any adverse event during the study. OFZ treatment as a single 30 mg/kg oral dose showed a 100% efficacy against F. hepatica. In conclusion, the trial described here demonstrated an excellent OFZ activity against F. hepatica in naturally infected pigs, after its administration at a single oral dose of 30 mg/kg.